"New" bronchopulmonary dysplasia and chronic lung disease. (September 2017) - Voynow, Judith A.
Abstract: Bronchopulmonary dysplasia (BPD) is the major cause of chronic lung disease and morbidity in preterm infants. Since it was first described fifty years ago, the epidemiology, pathogenesis, and treatment for BPD has changed dramatically. This review summarizes these changes and the clinical outcomes for infants diagnosed with BPD.